The Influence of NPF, ROA, CAR and FDR On The Financial Distress Of Sharia Bank in The Indonesia Period 2017-2022 - Muannasa, Aulia; Muntazeri, Eliya Najma; Rahmawati, Lilik (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2023)
This study aims to see how Non-Performing Financing (NPF), Return on Assets (ROA), Capital Adequacy Ratio (CAR), and Financing to Deposit Ratio (FDR), affect Financial Distress with the Altman Z-Score method approach. The sample of this study used a purposive sampling method and obtained 10 Islamic commercial banks in Indonesia for analysis. The data in this study comes from the annual reports of Islamic Commercial Banks. This study will be analyzed with a panel data regression model. The results of this study indicate that the Capital Adequacy Ratio (CAR) has a significant positive effect on financial distress, while NPF, ROA, and FDR have no significant effect on financial distress during the 2017-2022 period.